Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3171/2012.8.peds11539
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of surgically treated juvenile patients with moyamoya disease

Abstract: Object Surgical revascularization is considered an effective treatment for juvenile patients with moyamoya disease (MMD). Yet the long-term outcome in surgically treated patients still needs to be clarified. More than 30 years have passed since the authors' department started intensively treating pediatric patients with MMD using indirect anastomosis techniques. In this study the authors surveyed the current status of these patients. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…In children, direct revascularization is frequently technically not feasible, whereas the response to indirect revascularization is excellent, although 1 or 2 weeks are required for stabilization of symptoms. Although objective evidence from randomized controlled clinical trials suggesting improved function following these procedures is still lacking, several studies examining the long-term outcome in children with MMD following revascularization surgery strongly suggest that surgical revascularization improves cerebral hemodynamics and reduces the incidence of subsequent ischemic events [21,22,23,25,26,27,28]. Similar to previous studies, TIAs rapidly decrease or disappear and strokes rarely recur after surgery in pediatric patients of our cohort.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In children, direct revascularization is frequently technically not feasible, whereas the response to indirect revascularization is excellent, although 1 or 2 weeks are required for stabilization of symptoms. Although objective evidence from randomized controlled clinical trials suggesting improved function following these procedures is still lacking, several studies examining the long-term outcome in children with MMD following revascularization surgery strongly suggest that surgical revascularization improves cerebral hemodynamics and reduces the incidence of subsequent ischemic events [21,22,23,25,26,27,28]. Similar to previous studies, TIAs rapidly decrease or disappear and strokes rarely recur after surgery in pediatric patients of our cohort.…”
Section: Discussionsupporting
confidence: 71%
“…Despite the varied clinical associations observed in this series, the modes of presentation, age at onset of symptoms, familial occurrence were similar to those reported in the Japanese and South Korean literature [17,19,21,22,23]. However, the ratio of female to male patients was 1:1 by chance in our Chinese cohort.…”
Section: Discussionmentioning
confidence: 48%
“…Our results indicating that more than 80% of patients had a favorable social outcome appear comparable to those of past studies, in which the frequency of patients with a normal intelligence quotient or capable of independent daily activities remained 63.5%-87%. 13,17,25,31 Nevertheless, our results, along with those of several pioneering studies, shed light on the salient issue of social adaptation in pediatric moyamoya disease. Nakashima et al reported that approximately 10% of patients had severe difficulty in social or school life because of intellectual impairment.…”
Section: Discussionmentioning
confidence: 94%
“…These repair the damaged brain tissue via multiple mechanisms. The GM-CSF treatment can promote growth of collateral arterial branches in the pia mater and reduce the area of cerebral infarction due to arterial occlusion in the brain, thus protecting the nerves Mukawa et al, 2012). Previous studies on cerebral ischemia have shown that multipoint skull drilling combined with mobilization of autologous BMSCs have a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%